Health Monitoring of Laboratory Animals in Breeding and Experimental Units - PETRIDOU, E. (Journal of the Hellenic Veterinary Medical Society, 2017)
The last decades the number of laboratory animals used in experiments was dramatically increased due to biomedical research development, while new needs were revealed. The animals used in experiments should be genetically defined and should have a certain health status. Only healthy animals should be used in experiments. The good health of the lab animals that are goingto be used in experiments and the maintenance of this good health during the whole period (before- during- in the end) of experimentation is of crucial importance. On the other hand, the good health of all animals (and of course lab animals) is always at a risk due to a variety of infections. These infections (clinical or subclinical) can influence the outcome of the experiment. Moreover, clinical disease may not be observed until the animal is stressed (e.g the experiment itself or other endogenous or exogenous factors). Depending upon the exogenous factor or the infectious agent a variety of biological parameters maybe influenced. Microbial infections may also lead to biological material contamination such as: tissue cultures, cell-lines, biological products (sera), while many of these infectious agents are zoonotic. In this case, the risk for the personnel (scientists, animal caretakers, technicians) is great. Not only in most European Countries, but also in the U.S.A., Canada and Japan, Health Monitoring Programs (HMPs) in lab animal facilities are performed. In 1994 and later in 2002 the Federation of European Laboratory Animal Science Associations (FELASA) published recommendations for the health monitoring of rodent and rabbit colonies in breeding and experimental units. In these recommendations a list of viruses, bacteria, mycoplasmas, fungi and parasites that lab animal facilities should be monitored for, is presented. Moreover, recommendations for the sampling frequency, the sample size and the diagnostic methodology are also given. By publishing these Recommendations FELASA aims to the harmonization of HMPs at least between the E.U. countries. Moreover, the need for accredited diagnostic laboratories involved in health monitoring is underlined.